Biological response of human osteosarcoma cells to Si3N4-doped Bioglasses. (5th December 2018) - Marin, Elia; Adachi, Tetsuya; Boschetto, Francesco; Zanocco, Matteo; Rondinella, Alfredo; Zhu, Wenliang; Bock, Ryan; McEntire, Bryan; Bal, Sonny B.; Pezzotti, Giuseppe
Abstract: In vitro and in vivo studies have recently shown that silicon nitride (Si3 N4 ) is an osseoconductive and potential osseoinductive biomaterial. Even though the amount of bone mineral produced by Si3 N4 was inferior when compared to commercial Bioglass ®, it strongly stimulated the production of extracellular matrix and collagen tissues. Consequently, this study was designed to determine if appropriate mixtures of Bioglass ® and Si3 N4 might improve the ratio of mineral apatite to its biological matrix. Commercial 45S5 Bioglass ® powder was mixed with 5 and 10 mol% Si3 N4 powder, followed by melting, cooling, crushing, and comminution. The composite powders had modified morphologies and chemical structures including a reduced average particle size, a reduction of oxygen in the SiO backbone structure, and trapped CO2 gas which was converted into calcium carbonate. When exposed to human osteosarcoma cells within an osteogenic medium, the 5 mol% Si3 N4 composite powder resulted in higher amounts of hydroxyapatite while the 10 mol% Si3 N4 powder provided in a more balanced combination of collagen and mineral fractions closer to the natural composition of native human bone. Graphical Abstract: Highlights: The addition of Si3 N4 to standard Bioglass reduced the amount of 2-not-bonding-oxygens in the silica structure. Si3 N4 doped Bioglass promoted the formation of higher amounts of bone tissue when compared to the undoped material. Si3 N4 doped Bioglass stimulated the production of higher amounts of osteopontin respect to osteocalcin. Bone tissue formed on Si3 N4 doped Bioglass showed higher amounts of biological matrix respect to the mineral fraction.